Dinamika Motivasi Intrinsik dan Ekstrinsik Santri dalam Menghafal Kosakata Bahasa Arab (Mufradat): Studi Kasus di Pondok Pesantren Bustanul Ulum Mlokorejo Jember - Nuril Anwar (Al-Ahruf (Journal for Arabic and Linguistics Education), 2025)
This study aims to analyse the dynamics of intrinsic and extrinsic motivation among students in memorising Arabic vocabulary (mufradat) at the Bustanul Ulum Islamic Boarding School in Mlokorejo, Jember. The research problem focusses on the complex interaction between these two types of motivation within the unique context of pesantren education. The research method used is qualitative with a case study approach, where data was collected through in-depth interviews, participant observation, and document analysis, and then analysed thematically. The research findings reveal that santri motivation undergoes a dynamic transformation, forming a "motivational trajectory," from extrinsic motivation (such as fear of punishment or shame) towards more internalised and intrinsic motivation, triggered by an awareness of the value and benefits of vocabulary for understanding yellow books and a pesantren environment that supports value internalisation. This finding highlights the importance of educational strategies that not only rely on external discipline but also actively build bridges towards intrinsic motivation.   Referensi Ainiwaerjiang, A., Jin, X., Xie, Z., Tian, T., & Dang, Y. (2025). Research on the multi-agent motivation coupling evolution and synergy improvement for farmland ecological protection in China. Environmental and Sustainability Indicators, 25, 100583. Arias Valencia, M. M. (2022). Principles, scope, and limitations of the methodological triangulation. Investigacion y Educacion En Enfermeria, 40(2). Baharun, S. (2025). Innovative Approaches to Teaching Arabic Vocabulary to Novice Learners. Lahjatuna: Jurnal Pendidikan Bahasa Arab, 4(2), 77–88. Basith, A., Nisa, N. I., & Syafaat, K. H. M. (2024). PENGARUH INTERAKSI EDUKATIF GURU SERTA DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR BAHASA ARAB, IV(Ii), 66–72. Belay, S., & Melesse, T. (2024). Exploring the link between teachers’ motivation for continuous professional development and professional learning communities: A structural equation modeling approach. Sage Open, 14(3), 21582440241281856. Cho, H. D. (2022). Relationship between tourism and heritage from a tourist perspective: Synergy, complementarity and antagonism. Current Issues in Tourism, 25(10), 1557–   Deci, E. L., & Ryan, R. M. (2012). Self-determination theory. Handbook of Theories of Social Psychology, 1(20), 416–436. Erlande, R., Komalasari, K., Taufika, R., Hardian, M., Fauzan, A., & Maharani, A. (2024). Membekali Warga Negara di Era Post-Truth: Peran Krusial Pendidikan Kewarganegaraan di Australia. ASANKA: Journal of Social Science and Education, 5(1), 61–78. Henry, A., & Thorsen, C. (2021). Teachers’ self-disclosures and influences on students’ motivation: A relational perspective. International Journal of Bilingual Education and Bilingualism, 24(1), 1–15. Kholiq, I. N., Maya, N., & Jamroh, B. (n.d.). Upaya Internalisasi Kitab Taklim Mutaallim Dalam Menanamkan Pendidikan Karakter Santri Asrama Al Ma’Muroh Pondok Pesantren Darussalam Blokagung. Li, C. (2023). Exploring L2 motivational dynamics among Chinese EAP learners in an EMI context from a socio-cultural perspective. Sage Open, 13(2), 21582440231172704. Li, F.-Y., Hwang, G.-J., Chen, P.-Y., & Lin, Y.-J. (2021). Effects of a concept mapping-based two-tier test strategy on students’ digital game-based learning performances and behavioral patterns. Computers & Education, 173, 104293. Ortiz-Garces, I., Govea, J., Andrade, R. O., & Villegas-Ch, W. (2024). Optimizing chatbot effectiveness through advanced syntactic analysis: A comprehensive study in natural language processing. Applied Sciences, 14(5), 1737. Rahimi, S., Tajaddini, M., & Fatehi Rad, N. (2022). Dörnyei’s Motivational Self-System Theory and EFL learners’ L2 Selves. Journal of Language and Translation, 12(2), 99–   Rizqiya, F. A., Winata, F. I., Lutfiyah, I., Setiyo, M. D. J., Rohmah, Z. M., Zulfa, Z., & Asitah, N. (2025). Strategi Pembelajaran Berbasis Motivasi: Kombinasi Intrinsik dan Ekstrinsik untuk Kesuksesan Akademis. Nusantara Educational Review, 3(1), 62–68. Sun, Z., & Mu, B. (2023). Motivating online language learning: exploring ideal L2 self, grit, and self-efficacy in relation to student satisfaction. Frontiers in Psychology, 14, 1293242. Wang, P., Ganushchak, L., Welie, C., & van Steensel, R. (2024). The dynamic nature of emotions in language learning context: Theory, method, and analysis. Educational Psychology Review, 36(4), 105.